FINTECH REVOLUTION: RESHAPING INVESTMENT DECISIONS AND STRATEGIES - Kumar, Rekha; Kolte, Ashutos (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The fintech industry, driven by advancements like robo-advisors and AI-driven platforms, has reshaped investment decision-making by delivering personalized and data-driven financial solutions. This study utilizes statistical techniques, including descriptive analysis, correlation, and trend analysis, to explore the adoption of fintech services for investment decision-making in India across individuals with different levels of financial literacy. Between 2018 and 2022, fintech investments recorded a compound annual growth rate (CAGR) of 39.39%. The descriptive analysis indicates a growing investor preference for digital financial products, reflecting increasing confidence in digital financial instruments. The correlation analysis reveals a strong positive relationship (r = 0.998) between financial literacy and fintech adoption. This suggests that individuals with greater financial awareness are more likely to utilize fintech platforms for investment purposes. Trend analysis further highlights a shift in investment behavior, with digital investment adoption rising from 15% in 2020 to 40% in 2022, while reliance on traditional financial advisors declined from 60% to 32% over the same period. These findings underscore the transition from conventional investment approaches to digital investment platforms. The study emphasizes the significance of financial education in promoting digital investment adoption and reinforcing financial inclusion. It also underscores the need for strategic financial literacy initiatives and robust regulatory frameworks to ensure the comprehensive and sustainable expansion of fintech services within India’s evolving financial landscape. The research is based entirely on secondary data sources.